Biometrics under Biomedical Considerations - Nait-Ali, Amine; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book addresses biometrics from a biomedical engineering point of view. Divided into five sections, it discusses topics including the influence of pathologies on various biometric modalities (e.g. face, iris, fingerprint), medical and security biometrics, behavioural biometrics, instrumentation, wearable technologies and imaging. The final chapters also present a number of case studies. The book is suitable for advanced graduate and postgraduate students, engineers and researchers, especially those in signal and image processing, biometrics, and biomedical engineering.
Introduction to Biometrics in clinical environment -- Newborn footprint identification -- Newborn Palmprint identification -- Face recognition in healthcare -- Fingerprint in healthcare -- Face Recognition and plastic surgery -- Effect of ageing on face analysis -- Face Ageing under health and behavioral conditions.-Iris Recognition by considering pathological cases -- Influence of skin disease on fingerprints -- Veins Pathologies in biometrics.
Keywords: Biomedical engineering; Biometric identification; Signal processing; Pattern recognition systems; Biomedical Engineering and Bioengineering; Biometrics; Signal, Speech and Image Processing; Automated Pattern Recognition